Improving Colloidal Stability of Sepiolite Suspensions: Effect of the Mechanical Disperser and Chemical Dispersant - Alves, Luís (2020)
To allow the use of fibrous-like clays, as sepiolite, in different applications, their disaggregation and the formation of stable suspensions are crucial steps to enhance their performance significantly, e.g., in cellulose nanofibrils/clay composite formulations, enabling an adequate mixture of the matrix and filler individual components. Three distinct physical treatments of dispersion (magnetic stirring, high-speed shearing, and ultrasonication) and four different chemical dispersants (polyacrylate, polyphosphate, carboxymethylcellulose, and alginate, all in the form of sodium salts) were tested to improve the dispersibility and the formation of stable suspensions of sepiolite. Two sepiolite samples from the same origin but with different pre-treatments were evaluated. The particle size and suspension stability were evaluated by dynamic light scattering, zeta potential measurements and optical microscopy. Additionally, the sepiolite samples were initially characterized for their mineralogical, chemical, and morphologic properties. Of the three physical dispersion treatments tested, the ultrasonicator typically produced more stable suspensions; on the other hand, the biopolymer carboxymethylcellulose showed a higher ability to produce stable suspensions, being, however, a smaller particle size obtained when polyphosphate was used. Remarkably, 47 out of 90 prepared suspensions of sepiolite stayed homogeneous for at least three months after their preparation. In sum, the combination of a high energy dispersing equipment with an appropriate dispersing agent led to stable suspensions with optimal properties to be used in different applications, like in the composite production.